(untitled) (Pulse, 2026)
Background: Carotid body tumors (CBTs) are rare, highly vascular neuroendocrine tumors originating from paraganglionic cells in the carotid bifurcation. Case Presentation: We report the case of a 21-years-young female who presented with a painless, gradually enlarging neck mass on the left side of her neck. Imaging studies, including ultrasound and contrast-enhanced computed tomography, confirmed the presence of a well-defined, hypoechoic mass at the left carotid bifurcation, displacing adjacent vessels. A multidisciplinary team planned surgical resection, guided by imaging, resulting in the successful removal of the tumor. Histopathological examination confirmed the diagnosis of a carotid body tumor. Conclusion: Although rare, carotid body tumors should be considered in the differential diagnosis of neck masses in young patients. Early diagnosis with appropriate imaging and meticulous surgical planning can make promising outcomes in carotid body tumors. Pulse Volume 17, Issue 2 2025; 20-24